Single-cell analyses reveal the dynamic functions of Itgb2+ microglia subclusters at different stages of cerebral ischemia-reperfusion injury in transient middle cerebral occlusion mice model - Zeng, Fanning; Cao, Jun; Hong, Zexuan; Liu, Yujun; Hao, Jie; Qin, Zaisheng; Zou, Xin; Tao, Tao (Frontiers in Immunology, 2023)
The underlying pathophysiological mechanisms of cerebral ischemia-reperfusion injury (CIRI) is intricate, and current studies suggest that neuron, astrocyte, microglia, endothelial cell, and pericyte all have different phenotypic changes of specific cell types after ischemic stroke. And microglia account for the largest proportion after CIRI. Previous transcriptomic studies of ischemic stroke have typically focused on the 24 hours after CIRI, obscuring the dynamics of cellular subclusters throughout the disease process. Therefore, traditional methods for identifying cell types and their subclusters may not be sufficient to fully unveil the complexity of single-cell transcriptional profile dynamics caused by an ischemic stroke. In this study, to explore the dynamic transcriptional profile of single cells after CIRI, we used scSTAR, a new bioinformatics method, to analyze the single cell transcriptional profile of day 1, 3 and 7 of transient middle cerebral artery occlusion (tMCAO) mice. Combining our bulk RNA sequence and proteomics data, we found that the Itgb2+ subclusters of microglia exhibited specific functions at three different time points after the tMCAO. Our further analysis revealed that the Itgb2+ microglia subcluster was mainly involved in energy metabolism, cell cycle, angiogenesis, neuronal myelin formation and repair at 1, 3 and 7 days after tMCAO, respectively. Our results suggested that Itgb2+ microglia act as a time-specific multifunctional immunomodulatory subcluster during CIRI, and the underlying mechanisms remain to be further investigated.